Library and information studies for Arctic social sciences and humanities - Acadia, Spencer; Fjellestad, Marthe Tolnes (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Library and Information Studies for Arctic Social Sciences and Humanities serves as a key interdisciplinary title that links the social sciences and humanities with current issues, trends, and projects in library, archival, and information sciences within shared Arctic frameworks and geographies. Including contributions from professionals and academics working across and on the Arctic, the book presents recent research, theoretical inquiry and applied professional endeavours at academic and public libraries, as well as archives, museums, government institutions, and other organisations. Focusing on efforts that further Arctic knowledge and research, papers present local, regional, and institutional case studies to conceptually and empirically describe real-life research in which the authors are engaged. Topics covered include: the complexities of developing and managing multilingual resources; working in geographically isolated areas; curating combinations of local, regional, national, and international content collections; and understanding historical and contemporary colonial-industrial influences in indigenous knowledge. Library and Information Studies for Arctic Social Sciences and Humanities will be essential reading for academics, researchers and students working the fields of library, archival and information or data science, as well as those working in the humanities and social sciences more generally. It should also be of great interest to librarians, archivists, curators, and information or data professionals around the globe"--
OCLC-licensed vendor bibliographic record.
Keywords: Information services -- Arctic regions; Library science -- Arctic regions; Indigenous peoples -- Documentation; Social sciences -- Research -- Arctic regions; Humanities -- Research -- Arctic regions; LANGUAGE ARTS & DISCIPLINES / Library & Information Science